Recombination and Meiosis - Egel, Richard (Springer, 2017)
Once per life cycle, mitotic nuclear divisions are replaced by meiosis I and II—reducing chromosome number from the diploid level to a haploid genome and recombining chromosome arms by crossing-over. In animals, all this happens during formation of eggs and sperm—in yeasts before spore formation. The mechanisms of reciprocal exchange at crossover/chiasma sites are central to mainstream meiosis. To initiate the meiotic exchange of DNA, surgical cuts are made as a form of calculated damage that subsequently is repaired by homologous recombination. These key events are accompanied by ancillary provisions at the level of chromatin organization, sister chromatid cohesion and differential centromere connectivity. Great progress has been made in recent years in our understanding of these mechanisms. Questions still open primarily concern the placement of and mutual coordination between neighboring crossover events (...)